Effect of oxygen levels in cellular activity. (December 2020) - Figueiredo, S.M.; Sousa, F.O.C.; Lopes, M.A.G.; Quinta-Ferreira, R.M.; Quinta-Ferreira, M.E.
Abstract: Energy for life is produced inside the internal human energy factory, the mitochondrion, where low oxygen levels are likely to be correlated with stressful behaviors. These include thriving for performance, competition and perfection. One way to build a sustainable society is to reduce the daily stress, allowing human energy to target the control of energy resources and environmental safeguarding. So, it is important to assess the impact of decreased oxygen (hypoxia) in the body, especially in the brain, as a small imbalance in brain activity can affect vital energy production essential for sustainable life activities. This work addressed fluorescence changes associated with the formation of FAD and of reactive oxygen species (ROS), evoked by different levels of hypoxia. Exposing the slices to 0% and 21% O 2, caused an increase in FAD autofluorescence. Upon reoxygenation (95% O 2 ) the 0% O 2 trace did not recover, while the 21% O 2 signal decreased reaching the baseline. In contrast, at 40% and 65% O 2 the FAD fluorescence decreased reversibly. Regarding ROS fluorescence, no significant changes were observed during the application of 0% and 21% O 2 . However, at 40% and 65% O 2, the signals were enhanced recovering partially when the initial oxygen level (95% O 2 ) was reintroduced.